(untitled) (Psicologia USP, 2007)
This paper presents an experience of the Investigation and Formation Program on Health and Work of public school teachers, developed at the Federal University of Espírito Santo. It brings into question the health of all the teachers who work in public schools in Serra, a city in the State of Espírito Santo, aiming to undo the triad "pain-displeasure-teaching work" experienced by the teaching-body. This work intends to advance the comprehension of the health-work relations at schools, and it also intends to investigate the strategies used by these workers when resisting the attempts to disqualify teaching work. It states the possibility of opening spaces for discussion in the daily lives of teachers so that the struggle for health becomes a cooperative net between subjects and schools in order to inaugurate other forms of performance in those establishments. Thus, this paper proposes a methodology of work which has been based on the ergologic approach, built at Provence University in AIX/France.